Design criteria development of septage recycling ponds - Arifin, Bastian; Chongrak Polprasert; Samorn Muttamara; Vigneswaran, S.; The Government of New Zealand (Bangkok : Asian Institute of Technology, 1982)
A pilot scale experiment was carried out to investigate the design criteria for septage recycling system. The system consisted of, anaerobic, facultative and fish pond in series. The septage was treated in anaerobic and facultative ponds, and effluent from facultative pond was introduced into the fish pond stocked with fish at a stocking density of 5 fish/sq. m. The experimental results revealed that anaerobic and facultative pond in series showed 95% COD (92.7% BOD) removal efficiency at the areal loading of about 4,000 kg COD/ha-day. The maximum allowable loading to the fish pond was found to be 200 kg COD/ha-day. The septage recycling system was found to be effective for bacteria removal. This system yielded 99.99% total coliforms removal.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1982
Keywords: Tanning -- Waste disposal